Comparing habitat configuration strategies for retaining biodiversity under climate change. Issue 2 (19th March 2013) - Mokany, Karel; Harwood, Thomas D.; Ferrier, Simon; Devictor, Vincent
Summary Establishing new conservation reserves is a key management response to promote the persistence of biodiversity under climate change. Although there are many approaches to designing reserves, quantitatively assessing the performance of alternative habitat configuration strategies in retaining biodiversity has been limited by the lack of suitable modelling frameworks. Here, we apply a new dynamic macroecological modelling approach to compare the outcomes under climate change for plant biodiversity in Tasmania (all 2051 species) when new conservation reserves are established according to four contrasting reserve design strategies: connectivity; aggregation; representativeness; and a balanced approach. The most effective reserve design strategy under climate change depended on the specific conservation goal. New reserves focussed on improving representativeness most effectively promoted regional gamma diversity; however, the aggregation and balanced strategies best promoted the mean area of occurrence across all species. As the modelled level of dispersal increased, the connectivity strategy became relatively less effective, and the aggregation strategy relatively more effective in retaining biodiversity. Synthesis and applications. Our results demonstrate that adherence to a single habitat configuration strategy, such as connectivity, is unlikely to result in the best outcomes for biodiversity under climate change. The best reserve design strategy under climate change will vary between regions due to unique combinations of attributes and between taxa due to contrasting dispersal abilities. Quantitative assessments, such as ours, are required to identify configurations that will best retain the biodiversity of each region under climate change.